Heritability studies of some cassava genotypes - Asante, K.; Dixon, Alfred G.O. (2002)
Three traits, namely root number (RTNO), root weight(RTWT) and fresh yield (FYLD) of some cassava genotypes wrer scored and analysed for heritability. The genotypes differed significantly for each of the tree traits. Generally heritability per replicate was above 50% indicating that the additive portion of the genetic variance might be high. Heritability per plot ranged between 69% and 86% which might indicate that non additive effect of the genotypic variance variance might be small. Phenotypic and genotypic variance differed significantly, which reflects an environmental influence on the genotypes. By assuming a 5% differential selection of the top population, an advance of 46.5%, 41.5%and 33.5% can be arrived at for RTNO, RTWT and FYLD respectively, over their population means. Correlation between the three traits was highly significant and positive.